Early modern concepts for a late modern world : Althusius on community and federalism - Hueglin, Thomas O. (Waterloo, Ont. : Wilfrid Laurier University Press, 1999)
Johannes Althusius (1557-1638) was a political theorist and a combative city politician who defended the rights of small communities against territorial absolutism. He designed a system of politics in which sovereignty would be shared and jointly exercised by a plurality of collectivities, spatial as well as social, on the basis of mutual consent and social solidarity. Early Modern Concepts for a Late Modern World places Althusius in the context of his times and explains the main features of his political thought. It also suggests, perhaps most significantly, why his theories continue to resonate today. Hueglin's use of sources is thorough and scrupulous and provides a new interpretation of Althusius' theory.
Introduction: Reconstruction, Relevance, and Context -- The Contextual World of Althusius' Thought -- Four Hundred Years of Althusius Controversy and the Need for a New Interpretation -- The Historical Context: The St. Bartholomew's Day Massacre, the Dutch Revolt against Spain, and the Rise of the Absolutist State -- Theoretical Consequences: Absolutism and Territorial Centralization -- Recourse to Alternative Traditions: Political Calvinism, Aristotle, and Germanic Communitarianism -- The Method: Politica Methodice Digesta Exemplis Sacris and Profanis Illustrata -- The Althusian System of Politics -- Consociation: The Principle of Political Community in a Civil Society -- Societal Federalism: A Compound Polity of Particular and Universal Citizenship -- Representation: Problems of Participation and Legitimacy in the Political Process -- Subsidiarity and the Division of Powers: The Balance between Autonomy and Solidarity -- Sovereignty: Organized Unity of Action and a Right to Civil Disobedience -- The Relevance of Althusius Today -- Conclusion: Lineage and Affinities.
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
eBooks on EBSCOhost
Keywords: Althusius, Johannes, -- 1557-1638.; Althusius, Johannes, -- 1557-1638.; Althusius, Johannes, -- 1557-1638; Althusius, Johannes, -- (1557-1638); Althusius, Johannes, -- 1557-1638.; Althusius, Johannes; Political science; Political science -- History; Federal government; Communities; Science politique; Science politique -- Histoire; Fédéralisme.; Communauté.; political science; federations; POLITICAL SCIENCE -- History & Theory; Communities; Federal government; Political science; Politische Philosophie; Science politique; Science politique -- Histoire; Fédéralisme.; Communauté; Lien social; Fédéralisme.; Philosophie politique; Théorie politique; History